Investigation of the attitudes of Greek consumers towards the biofuel's consumption using social acceptance theory. Issue 1 (2nd January 2023) - Mouzaidis, Paschalis; Tsatiris, Michael; Damalas, Christos; Tsantopoulos, Georgios; Katsileros, Anastasios; Milis, Chrysostomos
Abstract: The present research is an attempt to investigate the Greek reality, regarding the social acceptance of biofuels, by identifying those factors on which it depends.A primary quantitative research was conducted, to which a structured questionnaire with closed-ended questions was used as the main research tool. The research sample consists of 150 Greek consumers, while 200 questionnaires were distributed giving a 75% correspondence percentage. Convenience sampling was used for the collection of the quantitative research data. The statistical analysis was done using SPSS (v. 23). Social acceptance of biofuels was the dependent variable. Energy factors (incentive and inhibitors), Economical factors (incentive and inhibitors), Environmental awareness and General inhibitors of biofuels consumption were used as independent variables. Kruskal Wallis, Mann Whitney and Spearman's correlation tests were conducted. Results showed that the social acceptance of biofuels in Greece depends on both the demographic data and the individual factors of the participants.Biofuel acceptance factors and the factors that frame their energy benefits depend on gender, with men scoring the above factors higher. Encouraging economic and energy factors and biofuel acceptance factors are dependent on employment status, while inhibitory factors depend on the area of residence of the participants. Environmental awareness, encouraging economic and energy factors, and biofuel acceptance factors are age-dependent, while economic factors (encouraging and inhibiting) and the acceptance of biofuels depend on the monthly income of Greek consumers. Finally, acceptance of biofuels, as well as the factors that frame it, depend on the educational level.